Al-Akhṭal’s Praise for Yazid Bin Mu’wiyah, the Second Caliph of the Umayyad Dynasty (680-683 AD) - Cahya Buana (Buletin Al-Turas, 2020)
This study intended to uncover the meanings contained in the context of praise in the ode poems of Al-Akhtal “Fa Aqsamtu La Ansā Yadae Al-Dahr” in qāfiyah bā intended for Yazid ibn Mu’āwiyah, the second Caliph of the Umayyad dynasty along with the context behind the text of praise. To reveal the meanings behind the text and the context of al-Akhtal's praise to Yazid, this study used a qualitative analysis method with a balagah and pragmatic approach. Based on the results of the analysis, it can be concluded that al-Akhtal in delivering his praise to Yazid used a style of language that was loaded with high eloquent elements, such as the style of terms, tasybīh, metaphor, majaz and kināyah. There were many deixis that could be used to reveal the context of al-Akhtal's praise for Yazid, both persona, time, place, discourse and social, such as the first-person singular nominative case personal pronoun, Umm Malik, Yazid ibn al-Muluk, Aba Khalid, Nu’mān, Ibn Hurrah, the days of Jillaq, Damasqus, Jazair Hamiz, Ahl 'Anah, and others. Al-Akhtal's praise for Yazid bin Mu’āwiyah was influenced by both similar behaviors. Both liked the world of freedom in terms of women and drinking to gain power in cruel ways. In addition, the as a Christian Al-Akhtal got more freedom in his life; while, Yazid did not care about religious values.